The organic chem lab survival manual a student's guide to techniques - Zubrick, James W. (Hoboken, NJ Wiley, 2016)
Written for the laboratory that accompanies the sophomore/junior-level courses in Organic Chemistry, Zubrick provides students with a valuable guide to the basic techniques of the Organic Chemistry lab. The book will help students understand and practice good lab safety. It will also help students become familiar with basic instrumentation, techniques, and apparatus and help them master the latest techniques such as interpretation of infrared spectroscopy. The guide is mostly macroscale in its orientation.
Safety First, Last, and Always -- Keeping a Notebook -- Mining your Own Data -- Jointware -- Microscale Jointware -- Other Interesting Equipment -- Pipet Tips -- Syringes, Needles, and Septa -- Clean and Dry -- Drying Agents -- On Products -- The Melting-Point Experiment -- Recrystallization -- Recrystallization: Microscale -- Extraction and Washing -- Extraction and Washing: Microscale -- Sources of Heat -- Clamps and Clamping -- Distillation -- Microscale Distillation -- The Rotary Evaporator -- Reflux and Addition -- Reflux: Microscale -- Sublimation -- Microscale Boiling Point -- Chromatography: Some Generalities -- Thin-Layer Chromatography: TLC -- Wet-Column Chromatography -- Refractometry -- Gas Chromatography -- HP Liquid Chromatography -- Infrared Spectroscopy (and a Bit of UV-VIS, Too ) -- Nuclear Magnetic Resonance.
Includes bibliographical references and index.
Keywords: Chemistry, Organic -- Laboratory manuals; Chemistry, Organic